Institutions and governance in Mozambique: A bird's eye view based on existing databases - Ines A. Ferreira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Using publicly available databases and drawing on a wide range of indicators, this paper reviews the institutional performance of Mozambique across seven broad categories: rule of law and judicial independence; voice and freedom of expression/association; political participation; accountability and transparency; political instability and violence, and external relations; state legitimacy and political leadership; and governance and state capacity. Overall, the selected indicators point to similar trends within each dimension and suggest limited progress during the last decades. Still, it is fundamental that these insights and the scores presented by the indicators are put into context, and that we understand the historical path of Mozambique, the internal and external factors at play, and the fact that it takes time for progress achieved to be reflected in this type of data.
Keywords: O43; O55; P00; 330; Mozambique; institutions; governance; indicators; databases